The Effect of Intraventricular Hemorrhage on Brain Development in Premature Infants: A Synthetic MRI Study - Zhang, Chunxiang; Zhao, Xin; Cheng, Meiying; Wang, Kaiyu; Zhang, Xiaoan (Frontiers in Neurology, 2021)
【Objectives】Synthetic MRI can obtain multiple parameters in one scan, including T1 ,T2 relaxation time ,proton density (PD), as well as brain volume, etc.This study aimed to investigate the parameter values T1 and T2 relaxation time, PD and volume characteristics of intraventricular hemorrhage (IVH) newborns brain. And the ability of synthetic MRI parameters T1 and T2 relaxation time and PD to diagnose IVH. 【Materials and Methods】The study included 50 premature babies scanned with conventional and synthetic MRI. IVH premature infants were allocated to the case group (n=15), and NON IVH (n=35).The T1, T2, PD values and brain volume were obtained by synthetic MRI. Then we assessed the impact of IVH on these parameters. 【Results】In posterior limbs of the internal capsule(PLIC), genu of the corpus callosum(GCC), central white matter(CWM),frontal white matter (FWM) and Cerebellum (each P<0.05), the T1 and T2 relaxation times of the IVH group were significantly prolonged. The significant differences also in PD. The brain volume in many parts were also significantly reduced , which was best illustrated in gray matter（GM）, cerebrospinal fluid and Intracranial Volume and brain parenchymal fraction (BPF) (each P<0.001, t=-5.232 to 4.596). The differential diagnosis ability of these quantitative values was found to be excellent in PLIC, CWM and Cerebellum (AUC 0.700-0.837, P<0.05). 【Conclusion】The quantitative parameters of synthetic MRI well show the brain tissue characteristic values and brain volume changes of IVH premature infants. T1 and T2 relaxation times and PD contribute to the diagnosis and evaluation of IVH.